PROGNOSTIC VALUE OF INTRATUMORAL CD57+T CELLS AND MICROVESSEL DENSITY IN HEAD AND NECK SQUAMOUS CELL CARCINOMA - Fraga, Carlos Alberto de Carvalho; Oliveira, Marcos Vinício Macedo de; Oliveira, Erica Silva de; Barros, Lucas Oliveira; Domingos, Patrícia Luciana Batista; Gomes, Érika Patrícia Pereira; Paula, Alfredo Maurício Batista de; Guimarães, André Luiz Sena (Archives of Oral Research, 2010)
OBJECTIVES: This study aimed to examine the association of CD57+ T cells and MVD withclinical parameters and prognosis of HNSCC. MATERIAL AND METHOD: In a restrospectiveanalysis, 43 cases of primary HNSCC have been studied. We also analysed CD57 and CD31counting. T and N parameters was analized by Binary logistic regression analysis. Survival wasanalysed by Cox regression analysis. RESULTS: CD31 was not associated with anyclinicopathological parameters. CD57 immunoexpression was associated with locorregionalpresence. Cox regression test showed correlation of worse survival with locorregional metastasispresence. For binary logistic parameter, WHO Grade parameter was associated with smaller tumorsize and absent metastasis CD57+ T cells count was relationed with worse survival.CONCLUSION: There was no association between MVD and clinicopathological parameters.Locorregional metastasis presenting high CD57 positivity. No association was found betweenCD57 and the other clinicopathological parameters. Multivariate analysis showed that individualspresenting locorregional metastasis were associated with poor survival. CD57 count and WHOgrade were associated with larger tumor size.